Eco-public art in pursuit of a sustainable green city and public space - Azhari, Syamim; Zakariya, Khalilah; Zainal Abidin, Norzalifa (2014)
Public art is an artwork or any visible component of art that embraces creativity and meaning, sited in public space. The emergence of public art in public space covers activities extending from functional, decorative, iconic, interpretive, integrated, ephemeral or temporary installation of artworks. Over the past thirty years, artists, designers and city planners have discussed and acknowledged the values and roles of public art that contribute to the public’s well-being. Public art involves the artist in creating the artworks and the public to participate, whether directly and indirectly. The contributions of public art from the aspects of social, cultural and economic perspectives have been well noted in public art projects and publications. However, studies that examine the environmental contributions of public art to the city are still very minimal. The aim of this paper is to review the existing public art and eco-public art projects and analyse how they can contribute to the environmental sustainability through their contents and process. The study is conducted through a literature review of books, journal articles and online resources, focusing on the sustainability, awareness and environmental values perceived and associated towards eco-public art. The findings outline the relationships of public art in public space and how it may lead to encourage further directions to contribute to the dialogue between art and the public, and environmental sustainability through public art programmes. This is essential in determining future directions of how public art might be approached towards achieving greener cities.